1614. Gwt1 Inhibitor, APX2104, Protects Against Invasive Aspergillosis in Neutropenic Mouse Model. (31st December 2020) - Shaheen, Shareef; Allen, John; Cole, D Chris; Asfaw, Yohannes; Juvvadi, Praveen; Shwab, E Keats; Kapoor, Mili; Shaw, Karen; Steinbach, William
Abstract: Background: Aspergillus fumigatus is the leading cause of invasive aspergillosis (IA), a lethal infection among immunocompromised patients. Guideline-recommended antifungal therapy against IA is a triazole antifungal, with other secondary options including an echinocandin and amphotericin B. Concerns about drug-host toxicity and antifungal resistance have been globally reported, so new, safe, and effective therapeutics are imperative. Methods: In vitro, CLSI standards were upheld as we tested APX2041, voriconazole, caspofungin, and amphotericin B against various A. fumigatus strains. In vivo we assessed toxicity and efficacy of APX2104 in immunocompromised mice respectively. Neutropenia was induced with 150 mg/kg of cyclophosphamide on days -2/+3 and 250 mg/kg of cortisone acetate on days -1/+6. Immunocompromised mice were infected in an inhalation chamber via 12 mL of aerosolized spores of A. fumigatus CEA10 at a concentration of 1x10 9 spores/mL (Day 0). Treatment started day +1 and ended day +7. Results: In vitro, APX2041, the active-form of APX2104, has over a 16-fold lower minimum effective concentration (MEC) when compared to voriconazole, caspofungin, and amphotericin B against various A. fumigatus strains, including echinocandin- and azole-resistant strains. In vivo, given preliminary pharmacokinetic data, APX2104 was tested in non-infected immunocompromised mice at 60 mg/kg and 78 mg/kg once per day (QD). Deaths due to toxicity were seen only at a dose of 78 mg/kg, so 60 mg/kg was set as a safe dose for our in vivo efficacy studies. In IA-challenged neutropenic mice, treatment with either posaconazole (20 mg/kg BID) or APX2104 (60 mg/kg QD) equally prolonged survival in 14 of 15 (93%) mice 14 days post-infection (p= 0.985). Untreatment control yielded a survival of 3 of 15 (20%) 14 days post-infection (p= < 0.001). Consistent with our survival studies, H&E and GMS histological samples also demonstrated that APX2104 treatment decreased fungal burden within the lungs of neutropenic mice when compared to the untreated group. Conclusion: Future studies will test the efficacy of APX2104 and posaconazole against azole antifungal resistant strains in vivo, as our preliminary findings suggest that APX2104 is a plausible solution to cure IA disease and combat antifungal resistance. Disclosures: All Authors : No reported disclosures